Role of community nurses in the prevention of tuberculosis in the Tshwane Health District of Gauteng - Siphiwe D. Mnisi; Mmapheko D. Peu; Salomé M. Meyer (AOSIS, 2012)
The objectives of this study were to identify the role of community nurses in the prevention of tuberculosis (TB) and to identify problems experienced by them when fulfilling this role in the Tshwane Health District of Gauteng. A non-experimental, descriptive, quantitative research design method was used to collect data from community nurses. The sample included 59 registered nurses who voluntarily agreed to participate in the study. A questionnaire was used to collect data and quantitative data analysis methods were employed. Various opinions and ideas on the role of community nurses in the prevention of TB and the problems experienced were identified. Based on the results of this research, measures to protect community nurses from contracting TB whilst on duty should be a priority. Government should support TB programmes by providing money to non-governmental organisations and direct observed treatment short course (DOTS) supporters to make follow-up visits to patients possible, thus reducing the number of defaulters. Stringent measures should be taken at all border points to ensure that foreigners are screened for TB, multidrug-resistant TB and extensively drugresistant TB. This study was limited to community nurses in the Tshwane Health District of Gauteng who were registered with the South African Nursing Council (SANC) and therefore this study could not be generalised to registered nurses in the hospital setting or even to clinics in the rest of South Africa.